Defining and targeting patterns of T cell dysfunction in inborn errors of immunity - Campos, Jose S.; Henrickson, Sarah E. (Frontiers in Immunology, 2022)
Inborn errors of immunity (IEI) encompass a group of more than 450 inherited disorders, often monogenic, that impair normal immune development and function. A subset of IEI yield impacts on immune function that include increased susceptibility to infection, autoimmunity, and malignancy, and are known as primary immune regulatory disorders (PIRD). While many aspects of immune function are altered in PIRD, one key impact is on T cell function. PIRD provide unique insight into T cell signaling by their nature; alterations in individual signaling molecules allowing tuning of relevant signaling pathway(s) in human cells. Quantifying T cell dysfunction, and the underlying mechanisms that cause it, in PIRD, is critical to identifying existing therapies and potential novel therapeutic targets to treat our rare patients and gain deeper insight into the basic mechanisms of T cell function. Though there are many types of T cell dysfunction, here we will focus on a key pathophysiological state known as T cell exhaustion. This state is classically found in chronic infection and malignancy, in both humans and mouse models of disease, where the chronic presence of antigen and inflammation induces a state of altered immunophenotype, transcriptional and epigenetic state and impaired T cell function. Since a subset of PIRD amplify TCR signaling and/or inflammatory cytokine signaling cascades, it is possible that they could induce T cell exhaustion by genetically mimicking chronic infection or chronic inflammation. Here, we review fundamentals of T cell exhaustion and its possible role in IEI in which genetic mutations mimic prolonged or amplified T cell receptor and/or cytokine signaling. Given the potential insight from the many forms of PIRD in understanding T cell function, and the challenges in obtaining primary cells from these rare disorders, we also discuss advances in CRISPR-Cas9 genome editing technologies and potential applications to edit healthy donor T cells. Editing T cells to contain patient genetic variants found in PIRD will allow investigations of mechanisms of T cell dysfunction in PIRD, including T cell exhaustion.